Pharmacokinetics and comparative metabolic profiling of iridoid enriched fraction of Picrorhiza kurroa – An Ayurvedic Herb. (2nd February 2017) - Zahiruddin, Sultan; Khan, Washim; Nehra, Rinki; Alam, Md. Javed; Mallick, Md. Nasar; Parveen, Rabea; Ahmad, Sayeed
Abstract: Ethno-pharmacological relevance: Picrosides I, II and apocynin are the main active principles present in the roots and rhizomes of Picrorhiza kurroa Royle ex. Benth (Kutki). Ethno-medicinally, the plant is used for the treatment of liver, upper respiratory tract disorders and dyspepsia, since long in Ayurveda. Aim of the study: This study attempts to determine the pharmacokinetic profile of picrosides I, II and apocynin in rats after oral administration of iridoid enriched fraction (IRF) and to recognize the pattern of its metabolites as such in IRF and in plasma. Materials and methods: A simple, precise, specific and sensitive RP-HPLC method was developed for simultaneous quantification of picrosides I, II and apocynin in rat plasma and in plant extract. Acetonitrile (ACN) and water was used as a solvent system with a gradient elution for pharmacokinetic studies using HPLC-PDA (Flow rate: 1.0 mL/min) and metabolic profiling through UPLC-MS (Flow rate: 0.5 mL/min) in selected reaction monitoring. A comparative study was performed in order to recognize the pattern and fate of metabolites in rat plasma up to 24 h after single oral administration of IRF. Results: Developed method produced more than 85% recovery of the targeted metabolites in rat plasma. The content of picrosides I, II and apocynin in IRF were found 5.7%, 18.3% and 27.3% w/w, respectively. The mean plasma concentration versus time profiles of picroside I, II and apocynin resulted in peak plasma concentration (Cmax ) 244.9, 104.6 and 504.2 ng/mL with half-life (t1/2 ) 14, 8 and 6 h, respectively. Other pharmacokinetic parameters such as time to reach Cmax (tmax ), area under curve (AUC), absorption (ka ) and elimination (ke ) constant, volume of distribution (Vd ) were also determined. Pattern recognition analysis showed fate of 18 metabolites in rat plasma up to 24 h out of 26 present in IRF. Conclusion: The information gained from this study postulates the basic pharmacokinetic profiling of picroside I, II and apocynin as well as fate of other metabolites after oral administration of IRF, demonstrating scientific basis of its traditional use in Ayurveda. Graphical abstract: